1986
DOI: 10.2165/00003088-198611040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Dapsone

Abstract: Dapsone (DDS) has for about 4 decades been the most important antileprosy drug. Concentrations of dapsone and its monoacetyl metabolite, MADDS, can be determined in biological media by high-performance liquid chromatography. After oral administration, the drug is slowly absorbed, the maximum concentration in plasma being reached at about 4 hours, with an absorption half-life of about 1.1 hours. However, the extent of absorption has not been adequately determined. The elimination half-life of dapsone is about 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
171
2
23

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(205 citation statements)
references
References 63 publications
9
171
2
23
Order By: Relevance
“…4K). The DDS dosage used in the C2C12 cells (20 μM) was optimized based on the observation that the long-term administration of DDS at standard doses (100 mg 20). Taken together, our results strongly suggest that the DDS effect is similar in worms and mammals.…”
mentioning
confidence: 66%
“…4K). The DDS dosage used in the C2C12 cells (20 μM) was optimized based on the observation that the long-term administration of DDS at standard doses (100 mg 20). Taken together, our results strongly suggest that the DDS effect is similar in worms and mammals.…”
mentioning
confidence: 66%
“…Uetrecht et al (1988) have demonstrated that dapsone may be oxidized in vitro by activated polymorphonuclear leucocytes to 4-amino-4'-nitro-diphenylsulphone via the toxic hydroxylamine and nitroso intermediates, which might account for the cell-specific toxicity observed. However, the incidence of agranulocytosis due to dapsone administration is idiosyncratic and relatively rare (< 1 in 2000), whilst methaemoglobin formation and reduction in erythrocyte life-span is dose-dependent and occurs to some extent in all subjects who take the drug (Zuidema et al, 1986).…”
Section: Inhibition Of Methaemoglobin Formationmentioning
confidence: 99%
“…Phenotyping with this drug has been shown to give results comparable with those using the elimination half-life of isoniazid or the urinary excretion ratio of acetylsulphamethazine to sulphamethazine (Gelber et al, 1971;Hanson etal., 1981). The plasma acetylation ratio of monoacetyldapsone (MADDS) to DDS at 3 h after a single oral dose of 100 mg of DDS is commonly used for phenotyping (Reidenberg et al, 1975;Clark, 1985;Zuidema et al, 1986). However, the possibility of using non-invasive urinary measurements has not been investigated systematically.…”
Section: Introductionmentioning
confidence: 99%